dmezzullo
Complete the Next Step: A partial solution to the equation 4d − 12 = 12 − 4d is given below. Choose the step that is missing from the solution.
4d − 12 = 12 − 4d
4d − 24 = −4d
3 = d
24 = −8d
−24 = 8d
−24 = 0d
−24 = −8d
Delete
Share
This Question is Closed
dmezzullo
Best Response
You've already chosen the best response.
2
@mikala1
mikala1
Best Response
You've already chosen the best response.
0
idk sorry
dmezzullo
Best Response
You've already chosen the best response.
2
the missing step is btween the 4d and the answer
dmezzullo
Best Response
You've already chosen the best response.
2
@RioAnne
mikala1
Best Response
You've already chosen the best response.
0
yes that is right
dmezzullo
Best Response
You've already chosen the best response.
2
@minnie123
dmezzullo
Best Response
You've already chosen the best response.
2
@kymber
minnie123
Best Response
You've already chosen the best response.
0
Oh I'm sorry I cant help on this one but I will recommend someone because she's a smart a#$ ... @aussy123
dmezzullo
Best Response
You've already chosen the best response.
2
@AriPotta
AriPotta
Best Response
You've already chosen the best response.
0
d
aussy123
Best Response
You've already chosen the best response.
0
Excuse me @minnie123, dont be rude
minnie123
Best Response
You've already chosen the best response.
0
Lol tough love, tough love @aussy123
Miyuru
Best Response
You've already chosen the best response.
0
\[4d-12=12-4d\]\[4d-12-12=-4d\]\[4d-24=-4d\]\[-24=-4d-4d\]\[-24=-8d\]\[3=d\]
aussy123
Best Response
You've already chosen the best response.
0
4d − 12 = 12 − 4d
4d − 24 = −4d subtract 4d on both sides
-4d -4d
___________________________________________
-24=-8d so It should be D
Miyuru
Best Response
You've already chosen the best response.
0
I have added some extra steps too..Find the missing one.. :D